T(w)o and fro: using the L1 as a language teaching tool in the CLIL classroom. Issue 4 (2nd October 2017) - Gallagher, Fiona; Colohan, Gerry
Abstract : This article describes a small in-class study which sought to explore the effectiveness (or not) of using the emerging bilingual skills of the students as a teaching and learning tool in a geography through English Content-Language Integrated Learning (CLIL) classroom in Northern Italy. In particular, the study sought to examine whether and to what extent the use of codeswitching/translanguaging between the native language and the language of instruction during content-related tasks might prove a useful technique for highlighting particular grammatical points in the CLIL vehicular language. Findings support the view that there is a place for the focused, planned and targeted use of the L1 during meaning-focused lessons in the language immersion classroom and that bilingual instructional techniques, such as the 'twisted dictation' used in the study, can be an effective means of both drawing students' attention to particular linguistic forms and of developing an enriched bilingual vocabulary. The authors suggest that the use of the L1 as a language teaching and learning tool is not limited to the CLIL or immersion classroom, but could be adapted for use in other language learning contexts.